Teatr awangardowy i japońska Nowa Fala - przypadek Terayamy - Loska, Krzysztof (Er(r)go. Teoria - Literatura - Kultura, 2013)
Krzysztof Loska Avant-Garde Theater and the Japanese New Wave—The Terayama Case The turn of the 50s in Japan is marked by a debut of a young generationof film and theater directors. Their artistic undertakings voiced an objection to an aesthetic tradition. Stage artists successfully cooperated with film makers as they shared a similar worldview, leftist sensitivity and their stance expressed the protest against political situation in the country. Film, like theatre, was used as a method of dealing with recent past, previous epoch’s militarism, and as a reflective tool, enabling contemplation over individual and national identity. In such a historical context a new kind of theater, called post-shingeki or Small Theaters Movement, rose to the surface. The purpose of this article, however, is not to discuss general characteristics of the then-current stage avant-garde but an analysis of a particular case, i.e. the works of Shūji Terayama whose most famous plays were staged at European festivals and by some were compared to works by Jerzy Grotowski and Peter Brook. For years Terayama remained a symbol of countercultural resistance as his shocking stagings and films, aroused controversy and outcry. The intention of the article is to present both sources of inspiration and cultural and political contexts that would facilitate a deeper understanding of Tarayama’s hermetic and problematic works whose purpose was to subvert art’s status in middle-class society, abolish constraints, and create a merger of theater and life.